2021
DOI: 10.1590/1519-6984.236827
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioaccumulation of PAH and BTEX in Malapterurus electricus (Siluriformes: Malapteruridae) and its Enteric Parasite, Electrotaenia malopteruri Sampled from Lekki Lagoon, Lagos, Nigeria

Abstract: Contamination of Lekki lagoon by petrogenic chemicals such as polycyclic aromatic hydrocarbons (PAH) and benzene, toluene, ethylbenzene, and xylene (BTEX) has been widely reported. The study was aimed at investigating the bioaccumulation of PAH and BTEX in Malapterurus electricus collected from Lekki lagoon in Lagos, Nigeria. BTEX was analyzed in the intestine, water, and sediment samples using 8260B Agilent 7890B gas chromatograph coupled to a mass spectrometer (GC-MS). While PAHs were tested in the same medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, Akinsanya et al, (2019) in a similar study reported that the parasite Wenyonia acuminata, infecting Synodontis clarias in the same study area did not bioaccumulate BTEX from fish. In another study by Isibor et al, 2020 the concentration of BTEX in the intestine of the Malapterurus electricus fish indicated that its enteric parasite Electrotaenia malopteruri significantly sequestered the toxicant's burden from the fish. Although the parasites were generally of low intensity in the fish, they, however, exhibited some ability to sequester chlorobenzene, ethylbenzene, o-xylene, m+p-xylene, and 1,4-dichlorobenzene from the intestine of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Akinsanya et al, (2019) in a similar study reported that the parasite Wenyonia acuminata, infecting Synodontis clarias in the same study area did not bioaccumulate BTEX from fish. In another study by Isibor et al, 2020 the concentration of BTEX in the intestine of the Malapterurus electricus fish indicated that its enteric parasite Electrotaenia malopteruri significantly sequestered the toxicant's burden from the fish. Although the parasites were generally of low intensity in the fish, they, however, exhibited some ability to sequester chlorobenzene, ethylbenzene, o-xylene, m+p-xylene, and 1,4-dichlorobenzene from the intestine of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides cans should therefore be burned in a proper incinerator designed for organochlorine waste disposal. In cases where this is not possible, efforts should be made to bury the materials in an approved dump or landfill [ 30 ] where there is no risk of contamination of surface or groundwater [ 31 ]. The most important recommended guide to the handling of lindane is total compliance with the local legislation regarding the disposal of toxic wastes.…”
Section: Discussionmentioning
confidence: 99%